Understanding Cultures, or Children’s Literature as a Tool for Developing Sensitivity to Multiculturalism - Pawlik, Paulina (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The text draws attention to the important role of the teacher in intercultural and inclusive education and the fact that intercultural fairy tales can significantly convey knowledge about cultural differences and tame the issue of Otherness. Providing students with cultural differences at the preschool and early school level and sensitizing them to the presence of the Other in the society around them will allow for the sustainable development of both native students and students with a migratory context. The author demonstrates these assumptions on the basis of the fairy tales Inny na uchodźczym szlaku by Anna Młynarczuk-Sokołowska and Katarzyna Szostak-Król and Podróż Innego do Krainy Smoka by Ewelina Rusicka-Karoui.